2017
DOI: 10.1080/17434440.2017.1389274
|View full text |Cite
|
Sign up to set email alerts
|

Computational methods for the aortic heart valve and its replacements

Abstract: Replacement with a prosthetic device remains a major treatment option for the patients suffering from heart valve disease, with prevalence growing resulting from an ageing population. While the most popular replacement heart valve continues to be the bioprosthetic heart valve (BHV), its durability remains limited. There is thus a continued need to develop a general understanding of the underlying mechanisms limiting BHV durability to facilitate development of a more durable prosthesis. In this regard, computat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
51
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 160 publications
(209 reference statements)
0
51
0
1
Order By: Relevance
“…A fluid-structure interaction (FSI) approach is necessary to model heart valves across the full cardiac cycle [8]. Accounting for coupling between the flexible valve leaflets and the fluid flow is crucial in studying the e↵ect of vortices in the aortic sinuses, predicting fluid-induced shear stress on the leaflets, and assessing valve performance by quantifying the valve orifice area and regurgitation [9]. A widely used approach to simulating cardiovascular FSI is the arbitrary Lagrangian-Eulerian (ALE) method [10,11], which uses body-conforming meshes for the fluid and solid.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A fluid-structure interaction (FSI) approach is necessary to model heart valves across the full cardiac cycle [8]. Accounting for coupling between the flexible valve leaflets and the fluid flow is crucial in studying the e↵ect of vortices in the aortic sinuses, predicting fluid-induced shear stress on the leaflets, and assessing valve performance by quantifying the valve orifice area and regurgitation [9]. A widely used approach to simulating cardiovascular FSI is the arbitrary Lagrangian-Eulerian (ALE) method [10,11], which uses body-conforming meshes for the fluid and solid.…”
Section: Introductionmentioning
confidence: 99%
“…Methods also have been developed that combine features of ALE and IB-like approaches, including the hybrid fictitious domain/ALE method [22] and the immersogeometric (IMGA) method [9,[23][24][25][26]. These methods also seek to relax the need to use body-conforming discretizations.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, many studies on computer simulation of the valve dynamics have been reported to provide valuable information on the functional analysis of native and THV as well as the relationship between mechanical stresses and disease progression [7][8][9][10][11]. Numerical simulations are also being used for the initial optimization and design of THV before the prototypes are built, and expensive experimental and animal evaluations have been conducted [12,13]. This can potentially reduce the time-to-market application of THV in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…Computational analysis is an important method widely utilized to study the biomechanic state of the aortic valve. Many decoupled FE and computational fluid dynamic (CFD) methods are commonly used to investigate the aortic leaflet dynamics [15]. However, the structural and hemodynamic responses of the aortic valve could not be calculated using both approaches due to the strong coupling effects between the blood and flexible leaflets.…”
Section: Introductionmentioning
confidence: 99%